Удмуртская Республика: путь к победе 1945 года: [монография] / Н. А. Родионов - Родионов Николай Анатольевич (2015)
Экземпляры: аб. ЦБ (11.12.2015) / Инвентарный номер: 2392 / Цена: 1296.31 / Авт.знак: Р 60 / ГРНТИ: 03 / ББК: 63.3 (2Рос. Удм) 622.1